2002
DOI: 10.1094/mpmi.2002.15.10.983
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression ofTsi1in Transgenic Hot Pepper Plants Enhances Host Resistance to Viral, Bacterial, and Oomycete Pathogens

Abstract: In many plants, including hot pepper plants, productivity is greatly affected by pathogen attack. We reported previously that tobacco stress-induced gene 1 (Tsi1) may play an important role in regulating stress responsive genes and pathogenesis-related (PR) genes. In this study, we demonstrated that overexpression of Tsi1 gene in transgenic hot pepper plants induced constitutive expression of several PR genes in the absence of stress or pathogen treatment. The transgenic hot pepper plants expressing Tsi1 exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 44 publications
0
38
1
Order By: Relevance
“…It was previously demonstrated that tobacco plants that overexpressed the PR1 gene exhibited higher tolerance to the aforementioned fungal pathogen (Alexander et al, 1993). Curiously, Shin et al (2002) held the opinion that transgenic pepper (Capsicum annuum) plants overexpressing the tobacco stress-induced gene Tsi1, which is involved in regulation of the PR1 gene, exhibited higher resistance to viral, bacterial, and fungal pathogens. The fact that PI plants also acquire higher resistance to viral, bacterial, and fungal pathogens may suggest that plants with higher resistance can be obtained by local transient infection with TMV; only single leaves of parental generation plants were infected with TMV, and infected leaves were removed 24 hpi.…”
Section: Higher Resistance To Stress Could Be a Results Of Enhanced Inmentioning
confidence: 99%
“…It was previously demonstrated that tobacco plants that overexpressed the PR1 gene exhibited higher tolerance to the aforementioned fungal pathogen (Alexander et al, 1993). Curiously, Shin et al (2002) held the opinion that transgenic pepper (Capsicum annuum) plants overexpressing the tobacco stress-induced gene Tsi1, which is involved in regulation of the PR1 gene, exhibited higher resistance to viral, bacterial, and fungal pathogens. The fact that PI plants also acquire higher resistance to viral, bacterial, and fungal pathogens may suggest that plants with higher resistance can be obtained by local transient infection with TMV; only single leaves of parental generation plants were infected with TMV, and infected leaves were removed 24 hpi.…”
Section: Higher Resistance To Stress Could Be a Results Of Enhanced Inmentioning
confidence: 99%
“…During the last decade, a considerable amount of research has indicated that overexpression of ERF family genes enhances the resistance of plants to environmental stress. For example, overexpression of ERF genes in chillies (Shin et al, 2002), Arabidopsis (Berrocal-Lobo et al, 2002), and tomato (Gu et al, 2002) improves plant disease resistance to viral and bacterial pathogens. The gene structure, phylogeny, and conserved motifs of the ERF gene family have been extensively studied in several species, including a genome-wide analysis in the model plants Arabidopsis and rice (Nakano et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, many ERF genes have been shown to enhance disease resistance when overexpressed in Arabidopsis or other species, including: ERF1 (Berrocal-Lobo et al, 2002;Berrocal-Lobo and Molina, 2004), AtERF1 and TDR1 of Arabidopsis (Heard et al, 2003; T.L. Reuber, K. Century, and K. Jakob, Mendel Biotechnology, unpublished data); Pti4 and Pti5 of tomato (He et al, 2001;Gu et al, 2002); Tsi1, NtERF5, and OPBP1 of tobacco (Park et al, 2001;Shin et al, 2002;Fischer and Droge-Laser, 2004;Guo et al, 2004); CaERFLP1 and CaPF1 of hot pepper (Capsicum annuum; Lee et al, 2004;Yi et al, 2004); GbERF2 of cotton (Gossypium barbadense; Zuo et al, 2007); HvRAF of barley (Hordeum vulgare; Jung et al, 2007); and TaERF1 of wheat (Xu et al, 2007). Encouragingly, in several cases, the overexpressed ERF TF provided enhanced resistance to multiple unrelated pathogens, which would be essential for a viable commercial product.…”
Section: Disease Resistancementioning
confidence: 99%
“…In addition, several ERF TFs that enhance disease resistance when overexpressed also enhance tolerance to various types of osmotic stress. The first published example of this phenomenon was the tobacco gene Tsi1, which was isolated as a salt-inducible gene, and found to enhance salt tolerance and resistance to Pseudomonas syringae pv tabaci when overexpressed in tobacco (Park et al, 2001), and resistance to several other pathogens when overexpressed in hot pepper (Shin et al, 2002). A number of other ERFs have now been shown to confer some degree of disease resistance and osmotic stress tolerance when overexpressed, including: OPBP1, which enhances salt tolerance (Guo et al, 2004); CaPF1, which produces freezing tolerance (Yi et al, 2004); CaERFLP1, which enhances salt tolerance ; HvRAF, which enhances salt tolerance (Jung et al, 2007); and TaERF1, which enhances drought, salt, and cold tolerance (Xu et al, 2007).…”
Section: Disease Resistancementioning
confidence: 99%